Legal Nature of the Joint Venture Contract - Pastor Argumedo, Reynaldo (1985)
This article analyzes the legal nature of the Joint Venture contract, highlighting its essential elements and characteristics. The Joint Venture is defined as an associative contract by which two or more persons associate to exploit a common business for a determined period of time, sharing profits and losses in a joint and unlimited manner. In addition, the elements that characterize it are addressed: the plurality of subjects, the affectio societatis, the profit motive, the participation in the losses and the personal nature of the associates. It is also emphasized that the contract has a plurilateral, commutative and successive tract nature, which leads to consider it as a sui generis contract. The author also discusses the administration, pointing out that all the partners participate in the control of the business, although there is the possibility of delegating the functions. Finally, the causes for dissolution of this contract are discussed, which include the end of the agreed term, the termination of the operation of the business, the death or incapacity of an associate, bankruptcy and the unlawfulness of the business.